A SEMANTIC ANALYSIS OF BEAUTY TERMS IN MAKE UP BOOKS - Ayuningtyas Putri Widyasari; Faiza Hawa; Sukma Nur Ardini (Universitas PGRI Semarang, 2022)
The study aimed to reveal beauty terms used in makeup books, and to find out the kinds of beauty terms found in the makeup books and their meanings. This study used qualitative method based on Miles and Huberman’s theory. The writers used semantics approach based on theory of kind of meaning by Wijana and Rohmadi (2008). In this study, the writers found 69 beauty terms in two makeup books written by international top makeup artists and influencers. Those terms were then clustered into makeup tool, makeup application technique, make up terms, and makeup mistake. The 69 terms belong to primer and secondary meaning. As primer meaning. lexical meaning gained 8 terms, denotative meaning gained 15 terms, and literal meaning gained 6 terms. On the other side, the rest is grammatical meaning, connotative meaning, and figurative meaning. Each of them gained 10 terms, 13 terms, and 17 terms. This study informed that most of the terms in the context of beauty have experienced change in semantics. Denotative meaning was the top among those meanings. In relation to the findings of the beauty terms found in this study, this confirms that beauty enthusiasts, as part of our community, have established their own vocabulary